Thermogravimetric Analysis of biosolids pyrolysis in the presence of mineral oxides. (October 2019) - Patel, Savankumar; Kundu, Sazal; Halder, Pobitra; Rickards, Lauren; Paz-Ferreiro, Jorge; Surapaneni, Aravind; Madapusi, Srinivasan; Shah, Kalpit
Abstract: Biosolids, the treated and stabilised sewage sludge, was pyrolysed in the presence of naturally occurring minerals in a Thermogravimetric Analyser (TGA). The results were then compared with a synthetic catalyst (i.e., 5% Co/Al2 O3 ). Higher mass loss was observed in TGA in the presence of both minerals and the metal oxide based catalyst when compared to biosolids' alone pyrolysis. The scanning electron microscope (SEM) images confirmed significant morphological changes in the produced biochars while Fourier Transform Infrared (FTIR) spectra corroborated noticeable chemical changes in their structure. The kinetic analyses conducted using a hybrid approach consisting of model-fitting and model-free methods, suggested that there was a reduction in activation energy in the presence of minerals and the catalyst. Overall, it is concluded that minerals despite their low catalytic activity, offer various process and morphological advantages. Highlights: Biosolids pyrolysis was studied in TGA employing natural minerals. A comparison with a synthetic metal oxide catalyst (i.e., 5%Co/Al2 O3 ) was established. The highest mass losses were observed in the presence of minerals and the catalyst. A reduction of ∼5–15% activation energy was noted with minerals and the catalyst. Minerals produced biochars with large pores when compares to the catalyst.